Novel filtenna for wireless applications. (2021) - Saxena, Shilpam; Sharma, Raghavendra; Upadhayay, Madhur Deo; Shrivastava, Apurv; Mishra, Pankaj Kumar
Abstract: A triple-band antenna integrated with three band-pass filters for 1.6 Gigahertz, 2.4 Gigahertz and 5.2 Gigahertz is presented. The Filtering antenna structure consists of three coupled line band-pass filters and a planar tri-band antenna with the partial ground of 9 mm × 25 mm. The proposed integrated system provides good filtering performance and these three frequencies are extremely helpful for L band, S band and C band applications. The projected antenna filter is fabricated on FR-4 epoxy substrate and its dielectric constant is 4.4, and thickness is 1.6mm